Vegetation Response to Disking on a Longleaf Pine Site in Southeastern Louisiana - Michael W. Olinde (National Quail Symposium Proceedings, 2017)
The effects of season (November vs February vs May) of disking on plant composition were evaluated on a longleaf pine (Pinus palustris) site in southeastern Louisiana during 1986-1990. Almost 150 species of plants were recorded in the fallow disked plots during 3 sampling years. Disked plots, compared to native upland pine sites, had a lower abundance of broomsedges (Andropogon spp.) and wiregrasses (Aristida spp.), more bare ground, and more early seral plants such as 3-seeded mercury (Acalyphya spp.) and poor-joe (Diodia teres). Legumes were reduced or stable under all disking regimes and disking did not increase the quantity of partridge pea (Cassia nictitans and C. fasciculata) or ragweed (Ambrosia artemisiifolia), as frequently reported.